Long-term pulmonary and extra-pulmonary consequences of COVID-19: A comprehensive review of current evidence and future perspectives - Wanjari, Mayur; Late, Sampada; Sharma, Ranjana; Munjewar, Pratiksha (Narra Sains Indonesia, 2023)
The global impact of the coronavirus disease 2019 (COVID-19) pandemic has been significant, affecting countless individuals worldwide. The existence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to considerable levels of illness and mortality. While considerable attention has been devoted to the immediate handling of COVID-19, there is a growing concern about the long-term effects of this disease. The recent studies have brought to light various complexities associated with COVID-19, encompassing both respiratory and non-respiratory problems such as lung scarring, heart diseases, neurological effects, and psychological consequences. The purpose of this review is to provide a comprehensive understanding of the persistent repercussions of COVID-19. It presents a summary of recent studies that have examined the frequency and severity of these complications, as well as an exploration of the potential mechanisms that contribute to their development. Specifically, it delves into the role of immune dysregulation, prolonged inflammation, and dysfunction of blood vessel linings in the origin of these complications. Moreover, the clinical significance of these long-term consequences is discussed, including their potential impact on healthcare systems and society as a whole. Our review highlights the necessity for continuous monitoring and management of patients diagnosed with COVID-19, along with the importance of conducting follow-up studies over an extended period to determine the most effective strategies for prevention and treatment of these complications.